2005
DOI: 10.1128/ec.4.10.1629-1638.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gene Genealogies Indicate that Two Clonal Lineages ofCryptococcus gattiiin British Columbia ResembleStrains from Other Geographical Areas

Abstract: Cryptococcus gattii has recently emerged as a pathogen of humans and animals in the temperate climate of Vancouver Island, British Columbia (B.C.). The majority (ϳ95%) of the isolates from the island belong to the VGII molecular type, and the remainder belong to the VGI molecular type. The goals of this study were to compare patterns of molecular variation among C. gattii isolates from B.C. with those from different areas of the world and to investigate the population structure using a comparative gene genealo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
121
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 41 publications
7
121
2
Order By: Relevance
“…Previous amplified fragment length polymorphism (AFLP) and multilocus sequence typing (MLST) studies have demonstrated that the Vancouver Island outbreak (VIO) is mainly caused by a single, hypervirulent genotype of C. gattii (AFLP6A/molecular type VGIIa) (8). Intriguingly, this genotype is not restricted to Vancouver Island but is also shared by, for instance, the CBS6956 strain (also known as NIH444 or ATCC32609, isolated from a patient in Seattle in 1971) and CBS7750 (isolated from a Eucalyptus tree in San Francisco in 1992) (11,12), suggesting that a recent genetic change has occurred within the VIO lineage, potentially as a result of an unusual same-sex mating event (12). However, the underlying molecular cause for the hypervirulence of this lineage remains unknown.…”
mentioning
confidence: 99%
“…Previous amplified fragment length polymorphism (AFLP) and multilocus sequence typing (MLST) studies have demonstrated that the Vancouver Island outbreak (VIO) is mainly caused by a single, hypervirulent genotype of C. gattii (AFLP6A/molecular type VGIIa) (8). Intriguingly, this genotype is not restricted to Vancouver Island but is also shared by, for instance, the CBS6956 strain (also known as NIH444 or ATCC32609, isolated from a patient in Seattle in 1971) and CBS7750 (isolated from a Eucalyptus tree in San Francisco in 1992) (11,12), suggesting that a recent genetic change has occurred within the VIO lineage, potentially as a result of an unusual same-sex mating event (12). However, the underlying molecular cause for the hypervirulence of this lineage remains unknown.…”
mentioning
confidence: 99%
“…Genotypic analysis revealed that virtually all environmental and clinical isolates belong to the VGII genotype of C. gattii (7). Studies using PCR fingerprinting, restriction fragment length polymorphism (RFLP) analysis, and amplified fragment length polymorphism (AFLP) analysis (7) identified two distinct genotypes among the isolates from Vancouver Island (VGIIa/AFLP6a and VGIIb/AFLP6B), which were later supported by multilocus sequence typing (MLST) (4,6). Given the close proximity, climatic and geographic similarities to Vancouver Island, and potential clinical importance, we have sought to determine whether this pathogenic microbe has spread to the Puget Sound area in the United States.…”
mentioning
confidence: 99%
“…The majority of cases in this outbreak were caused by C. gattii of the clonal subtype VGIIa, with a minority of isolates caused by the clonal subtype VGIIb (12,17,18), but other subtypes have also been isolated during this ongoing outbreak (17).…”
mentioning
confidence: 99%